Penyusunan Instrumen Penilaian Kognitif Berbasis HOTS Melalui Problem Based Learning dan Peer Assessment - Rahayu Pujiastuti; Luluk Isani Kulup (Indonesian Language Education and Literature, 2021)
This study aims to describe: the problems of the PBI Study Program students when compiling the HOTS-based cognitive assessment instrument, the application and improvement of students' abilities in preparing the HOTs-based cognitive assessment instrument after implementing problem-based learning and peer assessment. This qualitative descriptive research is subject to PBI Study Program students, Adi Buana University PGRI Surabaya. Data were collected through questionnaires, observation, documentation, and test techniques. Data analysis used descriptive and explanation techniques based on percentages. The results of this study, namely: discrepancies in compiling text-based instruments to inaccuracies in making assessment rubrics, problem-based learning, and peer assessment, can improve the learning process as evidenced by student activities and responses; and the ability to develop HOTs-based cognitive assessment instruments increased from 'poor' to 'good' criteria.Penelitian ini bertujuan untuk mendeskripsikan: permasalahan mahasiswa Prodi PBI pada saat menyusun instrumen penilaian kognitif berbasis HOTS, penerapan serta peningkatan kemampuan mahasiswa dalammenyusun instrumen penilaian kognitif berbasis HOTs setelah menerapkan problem based learning dan peer assessment. Penelitian deskriptif kualitatif ini bersubjek mahasiswa Prodi PBI, Universitas PGRI Adi Buana Surabaya. Data dikumpulkan melalui teknik angket, observasi, dokumentasi, dan tes. Analisis data menggunakan teknik deskripsi dan eksplanasi berdasarkan persentase. Hasil penelitian ini, yaitu: ketidaksesuaian dalam menyusun instrumen yang berbasis teks hingga ketidaktepatan membuat rubrik penilaian, problem based learning dan peer assessment dapat meningkatkan proses pembelajaran yang terbukti dari aktivitas dan respons mahasiswa; dankemampuan menyusun instrumen penilaian kognitif berbasis HOTs meningkat dari kriteria ‘kurang’ menjadi ‘baik’.